Interictal spiking in adult newly-diagnosed focal epilepsy of unknown cause: The effect of age. Issue 8 (August 2015) - Arbasino, Carla; Calorio, Federica; d'Orsi, Giuseppe; Marchioni, Enrico; Tartara, Elena; Marchese, Daniele; Rustioni, Valter; Moglia, Arrigo; Galimberti, Carlo Andrea
Highlights Elderly subjects with recent-onset, non-symptomatic focal epilepsy show a significant propensity to express interictal epileptiform abnormalities mainly during NREM 3–4 sleep. Age per se seems to affect this peculiar spiking pattern. This observation might be useful when choosing EEG recording procedures in the presence of suspected recent-onset focal epileptic seizures.